Water metering in piped community-based water supply systems: the challenge of balancing social and economic benefits. Issue 6 (18th August 2021) - Tantoh, Henry Bikwibili
ABSTRACT: This study examines the challenge of balancing the social and economic benefits of community-based water supply due to the introduction of water meters. One hundred and fifty-four questionnaires were disproportionately administered to users and 20 in-depth interview discussions were conducted with water stakeholders. Resistance to and destruction of water meters coupled with irregular monthly contributions towards operation and maintenance of the water system was identified. The introduction of water meters is seen by some as a money-making venture contrary to community-driven development norms. Balancing the social and economic benefit of water supply will improve community wellbeing, build resilience and sustainability.